Mobile home resident evacuation vulnerability and emergency medical service access during tornado events in the Southeast United States. (August 2019) - Strader, Stephen M.; Ash, Kevin; Wagner, Eric; Sherrod, Chayla
Abstract: Tornado mortality is greatest in the Southeast United States (U.S.) due to an elevated tornado risk, a larger total developed land area, and a greater number of mobile and manufactured homes. The National Weather Service (NWS) and Federal Management Agency (FEMA) both recommend that mobile home residents evacuate to a nearby sturdier structure when tornado threats arise. However, previous research has indicated that less than 30% of mobile home residents evacuate their homes during tornado events despite their expressed willingness to flee. This study employs geospatial near and network analysis techniques from mobile and permanent homes to nearby potential sheltering locations to determine possible reasons for the less than ideal sheltering rates. Additionally, emergency medical service response times for mobile and permanent homes are also assessed using a network analysis methodology. Results indicate that the distances and travel times from mobile homes to shelters are significantly greater than that of permanent homes to shelters. The distances and travel times from first responder stations to mobile homes are also greater compared to those associated with permanent home residents. Findings from this research illustrate that in addition to mobile home residents being more physically and socioeconomically vulnerable to tornadoes, they are also disproportionally less served by potential sheltering locations and emergency services due to being located more commonly in rural areas, especially in southern Alabama. Outcomes from this study may also be utilized by emergency managers and policy makers to refine and implement new tornado preparedness and mitigation plans within southeastern U.S. communities.